KONFLIK DALAM PENERIMAAN SISWA BARU (STUDI KASUS SEKOLAH DASAR PEMBINA NEGERI TULANGAMPIANG DI KOTA DENPASAR) - Candra Kartika Pratiwi, Anak Agung Putu; Suka Arjawa, I Gusti Putu Bagus; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
One of the educational institutions namely SDPN Tulangampaiang Denpasar has experienced a conflict, the school that should be a place to take knowledge now instead turned into a conflict factor. The conflict is caused by there is a person who intervened in taking the policy which done by the school. Furthermore, the acceptance of freshmen at SDPN Tulangampiang is used as an opportunity to obtain money by the person. The person would not be able to intervene without the permission of the power holders in PemecutanKaja Village. The problems of this research were: 1) why there is a freshmen acceptance conflict at SDPN Tulangampiang, 2) how is the mechanism of SDPN Tulangampiang party in handling the problem of freshmen acceptance, 3) how is the social impact of the conflict at SDPN Tulangampiang. The aim of this research was to find out the answer of those problems by using qualitative method. The theory used to analyze the data was theory of Society Conflict by Ralf Dahrendorf. The result showed that the freshmen acceptance conflict was caused by the village partyinsisted the school to accept the children in PemecutanKaja Village; in addition, it seen to be a chance to obtain an advantage by certain person. The mechanism that has been done was mediation between the banjar party and the school facilitated by the Village, the social impact of the conflict was the change of rules due to policies that made by the village’s headwho has the authority. The conclusion of this research was that the conflicting group was not exposed by media. Keywords: Conflict, freshmen acceptance